CHILDREN’S LANGUAGE DEVELOPMENT IN LEARNING SPEAKING AND LISTENING - Luli Sari Yustina (Institut Agama Islam Negeri Imam Bonjol Padang, 2012)
When observed the children’s learning and their development, teachers need to understand what they see. The process of observing, noting, and recording, with the support of record like the Primary Language Record, helps to develop powers of observation, but also directs attention to what is significant in a child’s behavior. The frameworks present in the Record help to structure these observations and provide the basis for a developing profile of a child’s strengths and need as a learner. There are five dimensions form part of a continuum of learning; they go on being important and developing throughout a person’s life as a learner: Confidence and independence, Experience, Strategies, Knowledge understanding, and reflectiveness. Classroom context is also considered for the young learners in opportunities and experiences. Copyright © 2012 by Al-Ta'lim All right reservedDOI: 10.15548/jt.v19i3.59